Phenotypic and Genotypic Characterization of Klebsiella pneumoniae Isolated From Retail Foods in China - Zhang, Shuhong; Yang, Guangzhu; Ye, Qinghua; Wu, Qingping; Zhang, Jumei; Huang, Yuanbin (Frontiers in Microbiology, 2018)
Klebsiella pneumoniae is not only a major hospital-acquired pathogen but also an important food-borne pathogen that can cause septicaemia, liver abscesses, and diarrhea in humans. The phenotypic and genotypic characteristics of K. pneumoniae in retail foods have not been thoroughly investigated in China. The objective of this study was to characterize K. pneumoniae isolates through biotyping, serotyping, determination of virulence factors, antibiotic resistance testing, enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR), and (GTG)5-PCR molecular typing. From May 2013 to April 2014, a total of 61 K. pneumoniae isolates were collected from retail foods in China. Using API 20E test strips, five different biotype profiles were identified among these isolates. The majority of isolates belonged to biochemical profile “5215773” (50 isolates, 80.6%). The capsular serotypes of the 61 K. pneumoniae isolates and one reference strain were determined by PCR. Of the seven capsular serotypes tested, four different capsular serotypes were identified. Serotypes K1, K20, K57, and K2 were detected in two, three, two, and one isolates, respectively. Serotypes K3, K5, and K54 were not detected. The presence of 11 virulence genes was assessed by PCR. The most common virulence genes were fimH (85.5%), ureA (79.0%), wabG (77.4%), uge (56.5%), and kfuBC (29.0%). ERIC-PCR and (GTG)5-PCR molecular typing indicated high genetic diversity among K. pneumoniae isolates. We identified 60 different ERIC patterns and 56 distinct (GTG)5 patterns. Genotypic results indicated that isolates carrying similar virulence factors were generally genetically related. Some isolates from the same geographic area have a closer relationship. The isolates showed high levels of resistance to ampicillin (51/62, 82.2%). Resistance to streptomycin (11/62, 17.7%) and piperacillin (10/62, 16.1%) was also common. The presence of virulent and antibiotic-resistant K. pneumoniae in foods poses a potential health hazard for consumers. Our findings highlight the importance of surveillance of K. pneumoniae in foods.